Contabilidade de Custos nas Autarquias Locais da Região Centro de Portugal - Jesus, M.; Laureano, Raul M. S.; Pedrosa, E. (XXIV Jornadas Luso Espanholas de Gestão Científica, 2014)
Municipalities need to adopt appropriate cost accounting systems (CAS) in order to obtain reliable information for decision making; The POCAL answered to this need, making mandatory cost accounting to calculate the costs of the functions, goods and services. Later other legislation was issued - RGTAL and LFL, reinforcing the need for applying cost accounting systems. So, the main objective of this study is to contribute for a better knowledge of cost accounting use in the Portuguese municipalities located at the central region. The empirical analysis was based on information collected through the technique of questionnaire survey. The research findings reveal that the majority of municipalities in the central region have adopted the CAS; the greatest number of municipalities adopted this system essentially following the RGTAL and LFL issuance. Furthermore, it appears that the educational factor is more explanatory of the adoption of this system.